Uniform nucleation of zincate layer through the optimized etching process to prevent failure in electroless plating on 2024 aluminum alloy. (June 2021) - Sharifalhoseini, Zahra; Davoodi, Ali
Graphical abstract: The role of an improper way to etch in the unsuccessful zincating and EN plating. Access to the optimum conditions for the growth of nanosize Zn layer with a uniform distribution on the overall surface results in the formation of the nickel coating with fewer pinhole defects. Highlights: The reason for the coating failure of the used 2024 Al alloy was explored. The optimized etching yielded the nanosize Zn layer on the overall surface of AA2024. The Ni layer with fewer pinhole defects and better anticorrosive action was achieved. Abstract: Double zincate treatment is of considerable importance to provide a reliable interconnection between the aluminum surface and upper coatings. In this work, we focus on etching as a crucial step prior to zincating to demonstrate the critical importance of optimized etching parameters in the improved uniformity of the zincate layer and Ni-P deposit. The morphology study of the commercial aluminum alloy, which was coated through the conventional procedure of Ni plating and failed in the salt fog test, raveled many defects in the zincate layer and Ni deposit. It was hence assumed that the improper etching is responsible for an incomplete zincation and therefore. With this regard, in etching step, two different HF:HNO3 ratios (25:75 and 5:95 vol/vol) and four different immersion times (15, 30, 45 and 60 s) were applied, and optimum conditions for the growth of nanosize Zn layer with a uniform distribution on the overall surface of the substrate were found. The considerable influence of this surface modification on the formation of a uniform nickel-plated layer with fewer pinhole defects and better anticorrosive action was discussed. Besides, the reason for the failure of the used commercial alloy in the common etching process was explored in this paper.